PENGARUH METODE EKSTRAKSI TERHADAP KADAR FLAVONOID TOTAL DAN KADAR FENOLIK DARI BUNGA TELANG (Clitoria ternatea L.) DENGAN METODE SPEKTROFOTOMETRI - Lestari, Ratih Guswinda; Suyono, Alip Desi; Suyono, Alip Desi (Jurnal Farmasindo: Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
Butterfly pea (Clitoria ternatea L.) is a leguminous plant known for its pharmacological benefits. The selection of an appropriate extraction method is crucial, as it determines the amount of secondary metabolites that can be effectively extracted. This study aims to evaluate the effect of different extraction methods on the total flavonoid and phenolic content of butterfly pea flower extract (EBT). Five extraction methods were used: maceration, percolation, digestion, reflux, and Soxhlet extraction, using 96% ethanol as the solvent. Extract evaluations included tests for drying loss, ash content, ethanol-soluble extract content, and heavy metal contamination. Phytochemical screening revealed that extracts from all methods contained similar secondary metabolites, including alkaloids, flavonoids, steroids, phenolics, tannins, saponins, and essential oils. The highest total flavonoid content was found in the extract obtained by the reflux method (109.13 mg QE/g extract), while the highest phenolic content was observed in the extract obtained by the digestion method (13.87 mg GAE/g extract).